The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00384-016-2669-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lymph flow patterns in splenic flexural colon cancers using laparoscopic real-time indocyanine green fluorescence imaging

Abstract: The findings of the lymph flow pattern of splenic flexure suggest that lymph node dissection at the root of the IMV area is important, and it may be not necessary to ligate both the lt-MCA and LCA, at least in cases without widespread lymph node metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(136 citation statements)
references
References 32 publications
2
124
0
1
Order By: Relevance
“…The mean age of the patients was 66 years which is the typical age group affected by CRC . Most of the studies included tumors of different anatomic locations except three studies; two of them involved patients with rectal carcinoma and one involved patients with splenic flexure carcinoma. Approximately 60% of the patients had an early stage CRC (TNM I‐II).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of the patients was 66 years which is the typical age group affected by CRC . Most of the studies included tumors of different anatomic locations except three studies; two of them involved patients with rectal carcinoma and one involved patients with splenic flexure carcinoma. Approximately 60% of the patients had an early stage CRC (TNM I‐II).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the SLN mapping, ICG NIR flouresence proved to be useful in evaluation of lymph flow patterns in patients with splenic flexure carcinoma. Watanabe et al applied real time ICG flouresence in 31 patients with splenic flexure tumors and reported that none of the patients exhibited lymph flow to the left colic artery and the left branch of the middle colic artery, concluding that ligation of both arteries is not mandatory. Moreover, none of the patients showed lymph flow directed to the pancreatic tail or the splenic hilum, therefore, the authors stated that routine distal pancreatectomy and splenectomy may not be necessary, at least in absence of widespread LN spread.…”
Section: Discussionmentioning
confidence: 99%
“…Watanabe et al . recently reported that lymphatic flow existed along the inferior mesenteric vein (IMV), in addition to along the left colic artery and middle colic artery, in splenic flexure cancer . Therefore, to perform optimal surgery for splenic flexure cancer, it would be useful to know the pattern of venous drainage preoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…Nishigori et al [28] found that ICG administered colonoscopically led to modification in the extent of mesenteric resection in nearly one quarter of patients and resulted in change of the colonic resection plan in nearly 17%. Watanabe et al [38] applied colonoscopically administered NIR ICG SLNM in 31 patients with splenic flexure cancers. They reported that none of these patients exhibited lymphatic flow to both the left colic artery and left branch of the middle colic artery concluding that routine ligation of both arteries is not required and that a tailored resection according to patient-specific drainage patterns could be appropriate.…”
Section: Resultsmentioning
confidence: 99%